Analisis Perlakuan Akuntansi Aset Biologis pada Perum Perhutani KPH Jember - Wiyasih Zerlinda; Indah Purnamawati; Yosefa Sayekti (UPT Penerbitan Universitas Jember, 2020)
Biological transformation consists of the processes of growth, development, degeneration, production and procreation which cause qualitative and quantitative changes in the life of these animals and plants. Measurement of biological assets is necessary for companies so that measurements are carried out fairly in accordance with the contribution of biological assets in generating output and profits for the company. PSAK 69 aims to regulate accounting treatment and recognition related to agriculture. This research uses a qualitative approach, in which this research is conducted with interviews with the relevant sections of this research. The technique of checking the validity of the data can be triangulated. According to Moleong (2012) triangulation is a data validity checking technique that utilizes something other than the data for checking purposes or as a comparison to the data. The results of the research at Perum Perhutani Jember that there are differences in measurements in the financial statements of Perum Perhutani Jember with measurements according to PSAK 69.